Runaway jury - Fleder, Gary.; Koppelman, Brian; Levien, David; Cleveland, Rick.; Chapman, Matthew, 1950-; Milchan, Arnon, 1944-; Mankiewicz, Christopher, 1940-; Cusack, John, 1966-; Hackman, Gene.; Hoffman, Dustin, 1937-; Weisz, Rachel, 1970-; Davison, Bruce, 1946-; et al. (Beverly Hills, California 20th Century Fox Home Entertainment, 2004)
After a man dies in a shooting incident, his wife files a lawsuit against the company that manufactured the gun. Her lawyer argues that the firm in question knew the shop which sold the weapon was not following federal regulations. As the case goes to trial, the firearm manufacturer takes no chances on the outcome, and they hire Rankin Fitch, a "jury consultant" who makes it his business to see that he knows enough about the jurors to be able to guarantee the result of the trial.
Special features: Anamorphic widescreen 2.35:1 -- Full-length audio commentary by director Garry Fleder -- Scene-specific commentary by Gene Hackman and Dustin Hoffman -- Deleted scenes with commentary -- 5 additional featurettes (Acting, Making-of, Cinematography, Production design, Editing) -- Language: English 5.1 Dolby surround ; Spanish Dolby surround ; French Dolby surround -- Subtitles: English, Spanish.
Dual layer.
Based on the novel by John Grisham.
Originally released as a motion picture in 2003.
Wide screen (2.35:1 aspect ratio).
Bonus features: full length feature widescreen version: director commentary by Gary Fleder; deleted scenes with optional commentary; selected scene commentary; exploring the scene - Hackman & Hoffman's first scene together; off the cuff: lead actor commentary by Dustin Hoffman & Gene Hackman; 5 featurettes: making-of, acting, cinematography, production and editing; man on fire trailer.
Music by Christopher Young ; music supervisor, Peter Afterman ; executive producer, Jeffrey Downer ; costume designer, Abigail Murray ; edited by William Steinkamp ; production designer, Nelson Coates ; director of photography, Robert Elswit.
Keywords: Jurors -- Drama; Spanish language materials; Jury -- Fiction; Tobacco industry -- Fiction; Legal stories; Closed caption video recordings; Videodiscs; Biloxi (Miss.) -- Fiction; Jurados; Legal drama; DVD-Video discs; Drama; Films for the hearing impaired; Feature films; Fiction films; Legal films; Thrillers (Motion pictures); Video recordings for the hearing impaired; Adventure films